Work Values and Job Rewards: A Theory of Job Satisfaction - Kalleberg, Arne L. (American Sociological Review, 1977)
This paper attempts to develop a theory of job satisfaction which incorporates differences in work values and perceived job characteristics as key explanatory variables. It empirically examines the relationship between job satisfaction and the work values and job rewards associated with six dimensions of work-intrinsic, convenience, financial, relations with co-workers, career opportunities and resource adequacy. It is found that work values have independent-effects on job satisfaction. The extent to which workers are able to obtain perceived job rewards is conceptualized to be a function of their degree of control over their employment situations. The paper also seeks to develop a framework which links the variation in the job satisfactions of workers to the factors that influence the degree of their control over the attainment of job rewards in American society. The analyses in this paper are based on data from the 1972-73 Quality of Employment Survey. The concept of job satisfaction traditionally has been of great interest to social scientists concerned with the problems of work in an industrial society. Many have been interested in job satisfaction, for example, as a result of a personal value system which assumes that work which enables satisfaction of one's needs furthers the dignity of the human individual, whereas work without these characteristics limits the development of personal potential and is, therefore, to be negatively valued. Thus, it is important to examine these issues in order, hopefully, to improve the work experiences of individuals as an end in itself. Other social scientists have been interested in this concept because of evidence that has linked the degree of satisfaction with work to the quality of one's life outside the work role-especially one's physical and mental health. Still others were motivated to study job satisfaction out of a desire to improve productivity and organizational functioning by improving the quality of work experiences of employees. While these concerns have their bases in different perspectives, they share the recognition of the importance of the job in the total life experience of the individual and the desirability of a